GIS-material for the archaeological project: Rävsjö - Planning of new wind turbine - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archeological report:
A new wind turbine with a connection road, a crane site and an electric cable that will be connected to a nearby power line, are planned within the property Rävsjö 1:1, Fivelstad parish, Motala municipality, Östergötland county. Several stone axes and other prehistoric remains have been found in the vicinity. The Swedish National Heritage Board's contract archeology division, UV Öst, has thus performed a preliminary investigation, conducted as an archaeological inspection, in April 2008. A total of 14 trenches were excavated on the field. A prehistoric hearth (RAÄ 85) was found in one of the trial trenches on the spot the wind turbine was planned. The hearth was excavated and interpreted as being solitary, since no other remains were found in the nearby trenches. The electric cable will be laid along an existing road and connected between the wind turbine and Rävsjö farm. Three trial trenches were excavated along the highest point of the cable stretch. In one of the trenches two hearths were found and excavated, of which one might be a furnace. The remains are probably part of the outskirt of a prehistoric settlement, of which the most part is judged to be located east of the road. The developer was able to avoid the the settlement remains (registered as RAÄ 84) and no further archaeological measures are thus suggested.

Purpose:

The information in the purpose is translated from the archeological report:
The aim of the preliminary investigation was to determine whether the construction of the new wind turbine would affect any archaeological remains. Any remains found were to be avoided, if possible, by locating the power line, road and wind turbine where the remains would not be damaged.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inom fastigheten Rävsjö 1:1, Fivelstads socken, Motala kommun, Östergötland planeras för ett nytt vindkraftverk, en anslutningsväg, en ny kranplats intill vindkraftverket och en elkabel som ska anslutas till närliggande kraftledning. I närområdet har flera stenyxor och förhistoriska lämningar påträffats. Riksantikvarieämbetet, UV Öst har därför utfört en arkeologisk förundersökning i form av antikvarisk kontroll i april 2008. Vid undersökningen grävdes totalt 14 sökschakt på åkermarken. En förhistorisk härd (RAÄ 85) påträffades i ett av sökschakten där vindkraftverket planeras. Härden har undersökts och tolkats vara ensamliggande då det i de närmaste intilliggande sökschakten inte påträffades några förhistoriska lämningar. Intill befintlig väg ska elkabel förläggas och anslutas mellan vindkraftverket och Rävsjö gård. Här grävdes tre sökschakt utmed sträckningens högsta punkt. I ett av schakten påträffades och undersöktes två härdar varav den ena kan vara en ugnskonstruktion. Förmodligen hör anläggningarna till utkanten av en förhistorisk boplats som till största delen bedömts ligga öster om vägen. Boplatslämningarna, registrerade som RAÄ 84, kunde undvikas vid kabelförläggningen vilket betyder att inga ytterligare arkeologiska åtgärder anses nödvändiga.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska förundersökningen var att konstatera om arbetet med vindkraftverket skulle beröra några fasta fornlämningar. Eventuella fornlämningar skulle i möjligaste mån undvikas genom att förlägga ledning, väg och vindkraftverk så att fornlämning inte skadades.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Rävsjö - Planering av nytt vindkraftverk
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi